Firm capability, corporate governance, and firm competitive behavior: A multi-dimensional framework - HE, Jinyu (Institutional Knowledge at Singapore Management University, 2009)
In this paper, we propose two possible remedies for corporate governance research. First, when examining the effects of corporate governance, researchers may want to simultaneously consider the role of firm resources and capabilities. Second, linking corporate governance with firm-level competitive behaviour rather than with firm-level performance may enable researchers to detect more nuances about the effects of corporate governance. We base our propositions on the notion that 'capability' and 'motivation' are the two fundamental drivers of firm competitive behaviour. Firm resources/capabilities, which correspond to the capability driver, define the potential level of a firm's competitive activity. Further, corporate governance, by virtue of affecting managers' motivation to take actions, moderates the relationship between firm resources/capabilities and competitive behaviour. In addition, viewing from the capability-motivation lens, we also observe that some elements of the corporate governance system supplement firm-level resources and capabilities, thus having direct effects on firm competitive behaviour as well.